Pelatihan Digital Marketing Warga Dusun Sidorejo, Ngestiharjo, Kasihan, Bantul, D.I Yogyakarta - Mursyid Mursyid; Yuliantoharinugroho Yuliantoharinugroho; Wilis Fahlefi; Agung Hartadi; Muhammad Isnaini Fathoni; Ngatipan Ngatipan (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
One of the problems faced by MSMEs in Sidorejo hamlet is marketing problems and skills in using technology. MSMEs in Sidorejo hamlet need technology-based business development so they can compete with new online businesses. The purpose of this writing is 1) Identifying the use of marketing media in MSMEs in Sidorejo Hamlet, Ngestiharjo Village. 2) Describe technology-based business development efforts in MSMEs in Sidorejo Hamlet, Ngestiharjo Village through digital marketing training. The method used to identify the use of marketing media is observation and interviews. The methods used in technology-based business development efforts are community education and training methods. Materials in efforts to develop technology-based businesses for MSMEs in Sidorejo Hamlet through digital marketing training include: 1) Cultivating an entrepreneurial spirit and providing inspiration from the success of online businesses, 2) Sharing sessions, 3) Digital marketing training. The identification results show that many MSMEs in Sidorejo Hamlet use simple technology in marketing, which is dominated by WhatsApp and Facebook media. In fact, there are still many MSMEs that run their businesses offline without the help of technology. The evaluation results of digital marketing training activities show that this activity received a positive response, was considered to provide insight and knowledge, and provide inspiration. Almost all business people want to practice this online business in developing their business.